Can Public Construction and Demolition Data Describe Trends in Building Material Recycling? Observations From Philadelphia - Marcellus-Zamora, Kimberlee A.; Gallagher, Patricia M.; Spatari, Sabrina (Frontiers in Built Environment, 2020)
There is a significant amount of waste generated during construction and demolition (C&D) activities, but few data to understand the sources, age, spatial origin, and its fate following entry into the waste management system. With few public records that track C&D waste flows, we turned to industry and Leadership in Energy and Environmental Design (LEED) to quantify C&D data and meta-data using material flow analysis (MFA). LEED databases are not normally used to build life cycle inventories or material flow accounts because they do not house sufficiently detailed data. We propose using the geo-referenced data on reused C&D waste in LEED databases to source parameters needed to build MFA models that support a circular building materials economy. By quantifying the change in C&D waste flow over years 2007–2017 and the diversion of materials from landfills from buildings in the United States City of Philadelphia, we found that, on average, 81% of total incoming waste was diverted from landfill and recycled into secondary materials markets. From LEED spatial data, we found that 77% of buildings sampled diverted C&D waste activities and installed building materials with recycled content. Although these findings describe material reuse metrics from different system boundaries in the built environment that cannot be statistically validated, they provide complementary data to describe C&D recycling performance benchmarks and incentive for future data collection to study and track trends in building material reuse. This case study highlights observations of C&D recovery and reuse from two separate but related operations, which could suggest that policies that incentivize C&D material reuse could promote a circular flow of building materials.